MIN 15 Aceh Tengah محاولات مدرسة اللغة العربية في ترقية قدرة التلاميذ على إتقان المفردات بـــــ (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
The purpose of this research is to find out the efforts of Arabic language teachers to improve students' ability in mastering vocabularies. The research method used is descriptive analysis. The data collection technique used is interview with Arabic language teachers. The data analysis techniques in this study use the theory of Miles and Humberman including: Data Collection, Data Reduction, Data Presentation and Drawing Conclusions. Arabic teachers' efforts to improve students' ability in mastering vocabularies consist of three aspects: (1) The use of strategies in vocabularies learning such as teaching vocabularies and making students listen to it, instructing students to repeat vocabulary, displaying pictures to understand the meaning of vocabularies, teaching vocabularies with appropriate songs on certain materials and repeating vocabulary at each class hour (2) The use of methods in vocabulary learning such as giving examples or the teacher displays something in accordance with the vocabularies to understand the vocabularies, playing simple roles, repeating the reading, using a vocabulary command and chain message game. (3) The use of media in vocabulary learning such as printed drawing media, blackboards and textbooks.
Keywords: efforts teachers; mastering vocabulary